1992
DOI: 10.1016/0014-5793(92)81093-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA base modifications in chromatin of human cancerous tissues

Abstract: Free rudi&induscd damegc to DNA in vivo is implicated to play II role in cwcinogcncris. Ewidcncc exists thal DNA dnmnpc by cndoynous free radiuls occurs in vivo, und thcrc is a rtcadpstatc lwcl of free radic&moditIcd hascs in ccllullrr DNA. WC hove invaligPtcd cndogcnous lcvcls of typical free rztdic&induscd DNA bits modifications in chromriz of various human cancerous tissues and their canswfrec rurrounding~issucr.Five different lypcr of sur@cally rcmovcd tirsucr were UK& nttmcly eolon, stomach. ovary, brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
101
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(112 citation statements)
references
References 46 publications
6
101
1
1
Order By: Relevance
“…Binding of metal-depeted ER to DNA was restored physiologival relevance of "OH radical induced DNA modifiby the addition of either 700 ktM zinc acetate or 140 ktM cations is an important one since "OH radicals have been native MT. Binding increased in a dose-dependent manner reported in many cancerous human tissues [23,24]. A recent in the presence of either zinc acetate or MT.…”
mentioning
confidence: 85%
“…Binding of metal-depeted ER to DNA was restored physiologival relevance of "OH radical induced DNA modifiby the addition of either 700 ktM zinc acetate or 140 ktM cations is an important one since "OH radicals have been native MT. Binding increased in a dose-dependent manner reported in many cancerous human tissues [23,24]. A recent in the presence of either zinc acetate or MT.…”
mentioning
confidence: 85%
“…Furthermore, many observations indicate a direct correlation between 8-oxoGua formation and carcinogenesis in vivo. 6,7,10,11 We have demonstrated elevated levels of typical free radicalinduced DNA base modification, including 8-oxoGua, in human cancerous colon tissues when compared to cancer free surrounding tissues. 6,7,12 These data were confirmed by Condo et al 13 who demonstrated higher amounts of 8-oxodGuo in colorectal carcinoma cells.…”
mentioning
confidence: 97%
“…In this regard, G to T transversions at TP53 mutational hot spots have been detected in several carcinomas (21)(22)(23). These mutations may be related to 8-oxoG, because elevated levels of 8-oxoG have been found in several carcinomas (24,25). Interestingly, formation of 8-oxoG at CpG dinucleotides in the gene promoter region inhibits the binding of methyl-CpG-binding proteins and the SP1 transcription factor (26,27).…”
mentioning
confidence: 99%